Lepidoptera of North America 19. Pawnee montane skipper Hesperia leonardus montana Skinner (Lepidoptera: Hesperiidae): habitat requirements, distribution and abundance, population responses to forest thinning and wildfire, and genetic investigations - Ellis, Scott, author; Sovell, John, author; Painter, Mikele, author; Drummond, Boyce A., editor; C.P. Gillette Museum of Arthropod Diversity, publisher (Colorado State University. Libraries, 2023)
This Contribution summarizes field studies conducted between 1985 and 2021 on the habitat and biology of the federally listed Pawnee montane skipper butterfly (Hesperia leonardus montana Skinner) and its population responses to forest thinning treatments and large wildfires within the same time frame. Other smaller studies and genetic information are also summarized. H. l. montana (Hlm) occupies a total known range of less than 80 square miles within the South Platte River drainage southwest of Denver, Colorado. Habitat consists of xeric conifer woodland dominated by an overstory of ponderosa pine (Pinus ponderosa), an understory of blue grama grass (Bouteloua gracilis), which is the larval foodplant, and dotted gayfeather (Liatris punctata), the primary adult nectar source. Peak adult Hlm densities during late August to early September generally ranged from 1 to 4 individuals per acre. Based on Hlm densities measured in 1986 belt transects, August abundance estimates ranged from 77,000 to 141,000 individuals within suitable habitat. If the Two Forks Reservoir were built, approximately 21 percent of Hlm suitable habitat would be inundated, and from 23 to 42 percent of the Hlm population would be lost, inferred from the 1986 skipper density measurements. The overall pattern of adult Hlm annual densities at the Trumbull forest thinning transects is interpreted as recovery from the 2001-2002 drought through 2007. Then density varied from year to year in response to both above and below average annual precipitation and temperature, but a general trend of increasing population size through 2021. Forest thinning treatments that were implemented at Trumbull from 2000 through 2004 are compatible with the continued survival of the skipper. A tree thinning pattern that preserves a conifer canopy cover of approximately 30 percent and 100 trees (5 inches or greater in diameter) per acre appears optimum for maintenance of Hlm habitat. Post-Hayman fire Hlm monitoring in moderately to intensively burned areas documents slow population recovery over time. Monitoring indicates that Hlm occurrence is negatively associated with standing dead trees, which may mean that intensively burned areas will remain sparsely inhabited over the long term. This avoidance behavior means that crown fires that kill all mature conifers represent a significant risk to the suitable habitat extent for this species. Genetic samples from Hlm and congeners were analyzed to investigate species and subspecies relationships and determine Hlm population substructure. Analysis of cytochrome c oxidase subunit I (COI) showed H. leonardus haplotypes are distinct from other Hesperia species, but it was not possible to distinguish H. leonardus subspecies from one another based on the observed COI haplotypes. Population structure analysis of Hlm samples using single nucleotide polymorphism (SNP) genotyping revealed gene flow throughout the range of Hlm, but clusters of more related individuals were distinguishable along a geographic gradient from north to south. Two individuals collected 4 miles south of the 1986 study area were noticeably different in the SNP analysis. The area includes remnants of ponderosa pine forest with blue grama and dotted gayfeather that survived the Hayman Fire. More investigation is needed to determine if this finding indicates an isolated subpopulation.
Pawnee montane skipper Hesperia leonardus montana Skinner (Lepidoptera: Hesperiidae): habitat requirements, distribution and abundance, population responses to forest thinning and wildfire, and genetic investigations
Keywords: Bouteloua gracilis; climate change; cytochrome c oxidase I; drought; forest restoration; haplotype; Hesperia leonardus montana; landscape genetics; Liatris punctata; population monitoring; ponderosa pine ecology; single nucleotide polymorphism; South Platte River; weather; wildfire; Lepidoptera -- Colorado; Butterflies -- Colorado